STUDY REGARDING THE ROLE OF THE BONE GRAFTING MATERIALS IN THE SUCCESS/FAILURE OF THE IMPLANT PROCEDURES - Tătaru Călin; Agop-Forna Doriana; Forna Norina (Romanian Dental Association for Education, 2019)
Aim of study. The study aims to determine if the type of graft materials influence the dental implants success rate in the proimplant surgical procedures used for the improvement of the bone support. Materials and method. The study group included 125 patients (65 females, 60 males, mean age 49.54 ± 11.387 years), selected from a private dental practice and from patients candidates to implantprosthetic therapy in Clinical Learning Base "M.Kogălniceanu" Iasi, of Faculty of Dental Medicine, U.M.F. "Grigore T.Popa" Iasi. All patients were diagnosed with extended partial edentation associated to atrophic alveolar bone and were firstly programmed for proimplant surgical procedures. Statistical analysis compared the group with favourable periimplant evolution with the group with peri-implant complications, and it was performed to evaluate the potential of each bone graft category to influence the success rate of the implant therapy. Results. Autogenous grafts were used more frequently in the patients group with positive evolution (10.0%) than in group with periimplant complications (7.6%), without significant statistical difference comparing to mixed grafts and xenografts. Conclusions. Regarding the predictability of the dental implants success rates, autogenous grafts offer an additional protection and higher success rate of dental implants comparing to xenografts or mixed grafts.